The conserved transmembrane proteoglycan Perdido/Kon-tiki is essential for myofibrillogenesis and sarcomeric structure in Drosophila - Pérez-Moreno, Juan J. (The Company of Biologists, 2014)
Muscle differentiation requires the assembly of high-order structures called myofibrils, composed of sarcomeres. Even though the molecular organization of sarcomeres is well known, the mechanisms underlying myofibrillogenesis are poorly understood. It has been proposed that integrin-dependent adhesion nucleates myofibrils at the periphery of the muscle cell to sustain sarcomere assembly. Here, we report a role for the gene perdido (perd, also known as kon-tiki, a transmembrane chondroitin proteoglycan) in myofibrillogenesis. Expression of perd RNAi in muscles, prior to adult myogenesis, can induce misorientation and detachment of Drosophila adult abdominal muscles. In comparison to controls, perd-depleted muscles contain fewer myofibrils, which are localized at the cell periphery. These myofibrils are detached from each other and display a defective sarcomeric structure. Our results demonstrate that the extracellular matrix receptor Perd has a specific role in the assembly of myofibrils and in sarcomeric organization. We suggest that Perd acts downstream or in parallel to integrins to enable the connection of nascent myofibrils to the Z-bands. Our work identifies the Drosophila adult abdominal muscles as a model to investigate in vivo the mechanisms behind myofibrillogenesis.